No strings attached: Corporate welfare, state intervention, and the issue of conditionality - Fabio Bulfone; Timur Ergen; Manolis Kalaitzake (Max Planck Institute for the Study of Societies, 2022)
This paper contributes to Comparative Political Economy (CPE), developing an analytical concept of corporate welfare. Corporate welfare - the transfer of public funds and benefits to corporate actors with weak or no conditionality - is a prominent form of state-business relations that CPE scholarship regularly overlooks and misinterprets. Such transfers should be understood as a structural privilege of business in a globalized post-Fordist capitalism, and an increasingly common strategy through which states attempt to steward national economic dynamism within a highly constrained range of policy options. However, without a well-developed concept of corporate welfare - premised upon the key criterion of conditionality - studies that identify a 'return' of the state in industrial planning misrepresent these transfers to business as a reassertion of state influence and control, rather than a reflection of state weakness and subordination. The paper provides the analytical building blocks to properly conceptualize transfers to business, works out the core challenges for empirical research, and provides empirical illustrations of this burgeoning phenomenon from the fields of unconventional monetary policy, privatization, and urban political economy. – – Der Aufsatz entwickelt ein analytisches Konzept der corporate welfare für die Vergleichende Politische Ökonomie. Corporate welfare - der Transfer öffentlicher Mittel an Unternehmen mit schwachen oder gar keinen Konditionalitäten - ist weitverbreitet und wird regelmäßig übersehen oder falsch eingeordnet. Solche Transfers sollten als strukturelles Privileg von Wirtschaftsunternehmen im postfordistischen Kapitalismus verstanden werden und als eine zunehmend verbreitete Strategie, mit der Staaten versuchen, wirtschaftliche Dynamik innerhalb eines stark eingeschränkten Spektrums politischer Optionen zu erzeugen. Ohne ein entwickeltes Konzept der corporate welfare - das auf dem Schlüsselkriterium der Konditionalität basiert - stellen Studien, die eine Rückkehr der Industriepolitik diagnostizieren, Transfers an Unternehmen fälschlicherweise als Wiederbelebung staatlichen Einflusses dar. Der Aufsatz liefert die analytischen Bausteine für eine angemessene Konzeptualisierung von Transfers an Unternehmen, arbeitet die zentralen Herausforderungen für die empirische Forschung heraus und liefert empirische Illustrationen des Problems aus den Bereichen unkonventionelle Geldpolitik, Privatisierungen und regionale Wirtschaftsförderung.
hdl:21.11116/0000-000A-5CC8-E
Keywords: 300; Comparative Political Economy; industrial policy; monetary policy; privatization; structural power; subsidies; Geldpolitik; Industriepolitik; Privatisierung; strukturelle Macht; Subventionen; Vergleichende Politische Ökonomie